Differentiation of Bos grunniens and Bos taurus based on STR locus polymorphism - K. B. Chekirov; Zh. T. Isakova; V. N. Kipen; M. I. Irsaliev; S. B. Mukeeva; K. A. Aitbaev; G. A. Sharshenalieva; S. B. Beyshenalieva; B. U. Kydyralieva (Вавиловский журнал генетики и селекции, 2023)
Differentiation of closely related biological species using molecular genetic analysis is important for breeding farm animals, creating hybrid lines, maintaining the genetic purity of breeds, lines and layering. Bos grunniens and Bos taurus differentiation based on STR locus polymorphism will help maintain the genetic isolation of these species and identify hybrid individuals. The aim of this study is to assess the differentiating potential of 15 microsatellite loci to distinguish between domestic yak (B. grunniens) bred in the Kalmak-Ashuu highland region (Kochkor district, Naryn region, Kyrgyz Republic) and cattle (B. taurus) of three breeds (Aberdeen-Angus, Holstein and Alatau) using molecular genetic analysis. The samples were genotyped at 15 microsatellite loci (ETH3, INRA023, TGLA227, TGLA126, TGLA122, SPS115, ETH225, TGLA53, BM2113, BM1824, ETH10, BM1818, CSSM66, ILSTS006 and CSRM60). Twelve of the loci were from the standard markers panel recommended by ISAG. Statistical analysis was performed using GenAlEx v.6.503, Structure v.2.3.4, PAST v.4.03, and POPHELPER v1.0.10. The analysis of the samples’ subpopulation structure using the Structure v.2.3.4 and 15 STR locus genotyping showed that the accuracy of assigning a sample to B. taurus was 99.6 ± 0.4 %, whereas the accuracy of assigning a sample to B. grunniens was 99.2 ± 2.6 %. Of the 15 STRs, the greatest potential to differentiate B. grunniens and B. taurus was found in those with the maximal calculated FST values, including BM1818 (0.056), BM1824 (0.041), BM2113 (0.030), CSSM66 (0.034) and ILSTS006 (0.063). The classification accuracy of B. grunniens using only these five microsatellite loci was 98.8 ± 3.4 %, similar for B. taurus, 99.1 ± 1.2 %. The proposed approach, based on the molecular genetic analysis of 5 STR loci, can be used as an express test in Kyrgyzstan breeding and reproduction programs for B. grunniens.